Association between passive smoking and respiratory illness: a case control study - S., Sreevishnu; M., Jesha Mohammedali; Haveri, Sheela P. (International Journal Of Community Medicine And Public Health, 2017)
Background: The adverse effect of passive smoking on human health and quality of life is a debatable matter. There is high risk of respiratory illness among spouses of smokers due to exposure to passive smoke. The objective of present study was to find an association between second hand smoke exposure and risk of developing respiratory illness in the last six months among married women aged 20 years and above and currently living together. Methods: A case-control study was conducted during a 6-month period (January to June 2016) among married women aged 20 years and above, who have been currently living with their husband for at least past two years in Perinthalmanna. Women with known respiratory disease such as bronchial asthma and tuberculosis were excluded. The sample size was calculated to be 87 cases and 87 controls. The cases were selected from the out-patient department of MES Medical College, Perinthalmanna, Kerala, India. The controls were selected from ward 28, Perinthalmanna. From each house only one female was interviewed. Results: The major symptoms in the cases were headache (35%), morning cough (34%) and chest pain (25%). The odds of having a respiratory illness when the husband is a smoker is 1.527 (95% C.I. 0.804 to 2.899) and the odds ratio increases to 4.7 (95% C.I.2.11 to 10.86) if the husband smokes at home. Conclusions: The study showed that the risk of having respiratory illness is higher in females when the husband is a smoker and the risk increases four times if the husband smokes at home.